Characterisation of freeze-dried type II collagen and chondroitin sulfate scaffolds. - Tamaddon, M; Walton, R; Brand, D; Czernuszka, J (2013)
Collagen type-II is the dominant type of collagen in articular cartilage and chondroitin sulfate is one of the main components of cartilage extracellular matrix. Afibrillar and fibrillar type-II atelocollagen scaffolds with and without chondroitin sulfate were prepared using casting and freeze-drying methods. The scaffolds were characterised to highlight the effects of fibrillogenesis and chondroitin sulfate addition on viscosity, pore structure, porosity and mechanical properties. Microstructure analysis showed that fibrillogenesis increased the circularity of pores significantly in collagen-only scaffolds, whereas with it, no significant change was observed in chondroitin sulfate-containing scaffolds. Addition of chondroitin sulfate to afibrillar scaffolds increased the circularity of the pores and the proportion of pores between 50 and 300 μm suitable for chondrocytes growth. Fourier transform infrared spectroscopy explained the bonding between chondroitin sulfate and afibrillar collagen- confirmed with rheology results- which increased the compressive modulus 10-fold to 0.28 kPa. No bonding was observed in other scaffolds and consequently no significant changes in compressive modulus were detected.